Autologous T-Cell-Free Antigen Presentation System Unveils hCMV-Specific NK Cell Response - Maria O. Ustiuzhanina; Maria A. Streltsova; Nikita D. Timofeev; Maxim A. Kryukov; Dmitriy M. Chudakov; Elena I. Kovalenko (Cells, 2024)
NK cells play a decisive role in controlling hCMV infection by combining innate and adaptive-like immune reactions. The hCMV-derived VMAPRTLFL (LFL) peptide is a potent activator of NKG2C+ NK cells. Proposed here is an autologous system of LFL stimulation without T lymphocytes and exogenous cytokines that allows us to evaluate NK-cell hCMV-specific responses in more native settings. In this model, we evaluated LFL-induced IFNγ production, focusing on signaling pathways and the degranulation and proliferation of NK cells orchestrated by microenvironment cytokine production and analyzed the transcriptome of expanded NK cells. NK cells of individuals having high anti-hCMV-IgG levels, in contrast to NK cells of hCMV-seronegative and low-positive donors, displayed increased IFNγ production and degranulation and activation levels and enhanced proliferation upon LFL stimulation. Cytokine profiles of these LFL-stimulated cultures demonstrated a proinflammatory shift. LFL-induced NK-cell IFNγ production was dependent on the PI3K and Ras/Raf/Mek signaling pathways, independently of cytokines. In hCMV-seropositive individuals, this model allowed obtaining NK-cell antigen-specific populations proliferating in response to LFL. The transcriptomic profile of these expanded NK cells showed increased adaptive gene expression and metabolic activation. The results complement the existing knowledge about hCMV-specific NK-cell response. This model may be further exploited for the identification and characterization of antigen-specific NK cells.